Post-independence Disillusionment: A Historical Reading of Ngugi wa Thing'o's Devil on the Cross - Singh, Ajita; Thakur, Ram Sebak (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
This paper undertakes to examine the post-colonial predicaments as limned in Ngugi wa Thiong'o's Devil on the Cross (1982). Reading the novel through a historical gaze, the researchers intend to explore the theme of neo-colonialism, economic exploitation, cultural alienation, and resistance in post-independent Kenya. Denouncing witheringly, Ngugi expresses his disenchantment with post-independent political system and government, wherein the neocolonial elites, in alliance with the white capitalists and new African leaders, monopolise the rewards of independence. The novel is an anatomisation of the lingering effects of colonialism, showcasing the horrenduous exploitation and marginalisation of the workers and the peasants at the hands of the elites, who as pawns of the white men perpetuate western domination. This research paper aims at justifying how Devil on the Cross is a powerful exegesis on the contradictions and struggles of a newly independent nation like Kenya still embroiled in colonial bequests. The theoretical approach to this research hinges on the theory of post-colonialism and neocolonialism, with special reference to the historical milieu of the contemporary Kenya. In doing so, the paper employs the basic tenets of post-colonialism — interrogating the Eurocentric political view and loudening the voices and experiences of the marginalised groups, and of neocolonialism — highlighting how the native elites, influenced and trained by their own former colonisers, align their economic interests and loyalties with the ex-colonisers, thereby forming specific mechanisms to create and continue power imbalance. This paper will explore also the concept of 'elitism' in the novel, and aid to the scholarly expansion of African post-colonial discourse.